Study of Essential Oil Isolated from Achiote (Bixa orellana) Leaves: Chemical Composition, Enantiomeric Distribution and Antimicrobial, Antioxidant and Anticholinesterase Activities - Eduardo Valarezo; Silvia Torres-Torres; Nohely Pineda-Guarnizo; Ximena Jaramillo-Fierro; Luis Cartuche; Vladimir Morocho; Miguel Angel Meneses (MDPI AG, 2023)
Bixa orellana is a native and cultivated species of Ecuador commonly known as achiote (annatto), this species is very versatile with a wide variety of uses and applications of its leaves, fruits and seeds. In this study, the chemical composition, enantiomeric distribution and biological activity of essential oil isolated from the leaves of Bixa orellana were determined. Hydrodistillation was used to isolate the essential oil. Gas chromatography coupled with mass spectrometry was used to determine the qualitative composition, a gas chromatograph equipped with a flame ionization detector was used to determine quantitative composition and gas chromatography on an enantioselective column was used to determine enantiomeric distribution. Antibacterial activity was determined using the broth microdilution method, for which we used three Gram-positive cocci bacteria, a Gram-positive bacilli bacterium and three Gram-negative bacilli bacteria. 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic (ABTS) acid radical cation and 2,2-diphenyl-1-picrylhydryl (DPPH) free radical were used as reagents for determining the antioxidant activity of the essential oil. The spectrophotometric method was used to analyze acetylcholinesterase inhibitory effect of the essential oil. The yield of leaves in essential oil was 0.13 ± 0.01% (v/w). A total of 56 chemical compounds, which represent 99.25% of the total composition, were identified in the essential oil. Sesquiterpene hydrocarbons were the most representative group in number of compounds and relative abundance with 31 compounds and 69.06%, respectively. The principal constituents were found to germacrene D (17.87 ± 1.20%), bicyclogermacrene (14.27 ± 0.97%), caryophyllene < (E)- > (8.56 ± 1.24%) and pinene <α-> (6.34 ± 0.13%). Six pairs of enantiomers were identified in the essential oil of Bixa orellana. The essential oil presented strong activity against the Enterococcus faecium (ATCC 27270) with an MIC of 250 μg/mL and weak activity against Enterococcus faecalis (ATCC 19433) and Staphylococcus aureus (ATCC 25923) with an MIC of 1000 μg/mL. The antioxidant activity of the essential oil was strong according to ABTS methods with a SC50 of 61.49 ± 0.04 µg/mL and was moderate in DPPH with a SC50 of 224.24 ± 6,4 µg/mL. Additionally, the essential oil reported moderate anticholinesterase activity with an IC50 of 39.45 ± 1.06 µg/mL.